De remedios y pócimas: las medicinas en el Quito del siglo 18 - Tapia Tamayo, Amílcar (2018)
Context: to know the history of the people, it is necessary to analyze their spirit and customs, by means of which they can understand their thought that identifies and values them by giving them their own reason for being. One of the most important activities is related to the way of preserving their health, vital foundation of life and existence. In this virtue, this analysis allows knowing the tradition of Quito related to the use of medicinal plants and their different applications.Objective: through this historical investigation, to detail the use of potions and medicinal plants used by the so-called doctors and healers of the eighteenth century Quito, in order to counteract the most common diseases affecting the people of Quito.Discussion and analysis: there are few historical and anthropological studies on the subject, which does not allow a comparative analysis in order to achieve better conclusions. Possibly the difficulty to access primary sources located in specialized files is the cause for this failure. On the other hand, social history related to Medicine is very relative, because historians have given little importance to such a valuable subject, which could well be understood in the eighteenth century thought. One of the reasons, probably, is related to the fact that for the time, those who were dedicated to cure, were despised, reason why the doctor's office was practiced by mestizos and people of lower middle class, which did not allow leave more written evidence in order to understand how diseases were treated and cured, being popular medicine, which subsists to our days, the only evidence to understand slightly the medical procedures practiced in the distant colonial century of our analysis.Conclusion: the history of Medicine in Ecuador has been treated on rare occasions by professional doctors, who have devoted themselves with admirable patience to collect all the details they have been able to locate; especially in the archives of the old San Juan de Dios hospital at the Ecuadorian capital. In the same way, they have been able to locate certain data that the social and political history of the country has not taken into account. For this they have resorted to the valuable historical archive of the Central University of Ecuador, which keeps and preserves true documentary gems about the Faculty of Medical Sciences. However, there are no specialized studies on the popular pharmacopoeia, a fundamental basis for understanding the state of health of the people of Quito who lived in the 18th century